STUDY OF POLYPHENOLIC COMPOUNDS IN JUJUBE (ZIZIPHUS JUJUBA MILL.) GROWN IN UZBEKISTAN - Zokirova, Mashhura; Gulomkhojaeva, Nargiza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This research provides information about the locally cultivated Ziziphus jujuba Mill. (Chinese jujube). In particular, the study presents its botanical description, chemical composition, biological characteristics, and an analysis of studies conducted by foreign scientists. In laboratory conditions, aqueous and alcoholic extracts of this fruit were obtained. After filtration, alcoholic extraction was carried out in the next stage. The contents of flavonoids and gallic acids in the extracts and concentrates were determined using high-performance liquid chromatography (HPLC). The obtained results are presented in tables.